Exploring Speech-Recognition Technology on English Pronunciation Skills: A Qualitative Study in Eleventh Grade of SMAI Miftahul Ulum - Moh. Hidayatulllah; Zainuddin Zainuddin; Beny Hamdani (Jo-ELT (Journal of English Language Teaching) Fakultas Pendidikan Bahasa & Seni Prodi Pendidikan Bahasa Inggris IKIP, 2025)
This study explores the use of speech-recognition technology to improve English pronunciation among eleventh-grade students at Miftahul Ulum Islamic Senior High School. Using a qualitative case study approach, data were collected through semi-structured interviews, classroom observations, and document analysis. Thematic analysis revealed five key findings: (1) improved segmental pronunciation accuracy, (2) increased student motivation and engagement, (3) challenges with accent recognition, (4) limited support for fluency and natural speech, and (5) a need for more personalized feedback. While the technology effectively corrected individual pronunciation errors and boosted learners’ confidence, its limitations in recognizing regional accents and supporting sentence-level fluency suggest the need for a more integrated instructional approach. The study recommends using speech-recognition tools as supplementary aids, combined with communicative activities such as group discussions or role-play. These findings offer important insights into technology-enhanced language learning in the Indonesian EFL context and highlight the need for more adaptive, linguistically inclusive speech-recognition systems.